Diversity and Conservation of Medicinal Plants around Madduvil Sivan Kovil Area, Northern Province, Sri Lanka - Nithiakumar, N. (The Department of Forestry and Environmental Science University of Sri Jayewardenepura, Sri Lanka, 2025)
Medicinal plants, growing naturally in diverse habitats, have been utilized in Siddha, Ayurvedic, and traditional medicine for over 5,000 years. This study focuses on the diversity and conservation of medicinal plants around the Madduvil Sivan Temple, located in the Meesalai Grama Sevaka Division J/312 Madduvil Maththi, Chavakacheri. Conducted from January 2024 to March 2024, the research identified a maximum of 113 roedicinal plant species across 23 families, including notable families such as Acanthaceae, Asteraceae, Cucurbita, Verbenaceae, Fabaceae, and Malvaceae and authenticated by the Department of Gunapadhan, Faculty of Siddha Medicine, University of Jaffna. Among these, several endemic species were documented, highlighting the unique and vulnerable biodiversity of the area. Based on morphological characteristics, the plants were classified as herbs (31.8%), shrubs (10.6%), creepers (9.7%), climbers (17.4%), and trees (30%). The parts used for medicinal purposes included roots (30 species), leaves (78), seeds (15), fruits (22), stems (5), bark (21), wood (5), latex (6), tubers (4), and whole plants (20). Further classification based on plant form included herbs (36), shrubs (12), creepers (11), climbers (20), and trees (34). The species were categorized into expectorant (7 species), diuretic action (6), diaphoretic (7), antiseptic (5), alternative action (3), and rejuvenation action (12) according to pharmacological action based on the traditional and literature validation, This study documented many medicinal plants, which is helpful for further research that leads to the discovery of new medicine and the preparation of siddha, ayurvedic medicine. Conservation of these medicinal plants is vital for future research, contributing to discovering new medicines and preparing Siddha and Ayurvedic formulations. The Northern Province Indigenous Department has initiated various conservation measures, including the establishment of herbal gardens in each district, promoting herbal gardens in schools, and encouraging home gardening. These efforts aim to preserve rich medicinal plant biodiversity for future generations.
Keywords: Medicinal plants; Siddha medicine; Diversity conservation; Diversity